Caracterização morfológica e enzimática de isolados de Corynespora cassiicola e reação de cultivares de soja à mancha-alvo - Ferreira Filho, Antônio Sérgio (2012)
Brazil appears as second producer of soybeans. Among the main factors limiting the production, we highlight the occurrence of soybeans diseases specially target spot caused by the fungus Corynespora cassiicola. The damage caused by the target spot can be reach 45%. Given the importance of this disease, this work was performed to characterize isolates from different regions of Brazil and know the reaction of some soybean cultivars with use of proposed methodology. It was found variability in the contour and shape of the spore isolates, as well as the enzyme degradation rates ranging from 1,1 to 2,7. The upper and lower threshold temperatures were respectively 40,4 and 0 °C and the optimum temperature calculated was 20,2 °C. To study the mycelial growth, sporulation and colonies colorimetric evaluation of isolates were used Petri dishes with seven different substrates - Potato Dextrose Agar (PDA), Czapek Solution Agar (CZP), Infant Food (AI), Vegetable Broth ( CH), carrot agar (CA) and Soy Extract (ES) and two light conditions. The color of colonies was assessed using the Munsell color chart and resuted a ranging from olive-dark gray (5Y3 / 2) to gray (5Y7 / 1). The mycelial growth was evaluated using a digital caliper and expressed in mm. Sporulation was estimated as number of spores per cm2 of each substrate and the light condition. The greatest growth and sporulation were obtained on substrates with Soy Extract performed with leaves, steams and pods of susceptible material (S-ES) and baby food (AI) under a photoperiod of 12 hours of light. To study the reaction of cultivars, we compared four inoculation techniques: M-1) inoculation on field; M-2) inoculation with 48 hours in a moist chamber post inoculation; M-3) inoculation with 48 hours in a moist chamber post inoculation associated with leaf wetness kept for overnight, simulating field conditions; M-4) detached leaves. Methods 3 and 4 had lesions with diameter sizes ranging from 2 to 14.3 (mm), similar to those obtained in the field. It was built a response curve for number of lesions in the central leaflet and lesion diameter (mm) for different conidia concentrations or mycelium macerated / mL. The conidia and mycelium macerated concentration/ mL of 45x103 and 50 x103 respectively showed a number of lesions, and lesion size satisfactory not occurring coalescence of lesions. For the reaction of cultivars were used BMX PotênciaRR, Hutcheson, M8336RR, M8360RR, M-Soy 8001, NK 7059RR (V-maxRR), TMG 113RR and two isolates (IS- 01/MG and MES307). Were evaluated defoliation ( %), incidence (%), number of lesions and lesion size (mm). The resistant cultivars were Hutcheson and NK7059RR and more susceptible were M-Soy 8001 and TMG113RR. Not found immune cultivar to target leaf spot